Functional evaluation of the diabetic athlete: Role of the sports doctor - Francavilla, V. C.; Polito, R.; Parisi, M. C.; Mingrino, O. G. M.; Campanozzi, A.; Daniele, A.; Messina, A.; Monda, V.; Valenzano, A. (Journal of Human Sport & Exercise, 2020)
Obesity is a multifactorial disease and the most primary risk of this is the development of type 2 diabetes. Numerous studies show that the effects of obesity on glucose metabolism result in the deterioration of glucose tolerance, the development of insulin resistance and the consequent damage of the secretory function of beta-cells. The type 2 diabetes is a worldwide health problem associated with obesity and sedentary lifestyle. As reported the American Diabetes Association, the physical activity is fundamental for type 2 diabetes patients, reducing blood pressure, cardiovascular events, and improve glucose metabolism and insulin sensitivity. In the light of these evidences, the aim of this study is to analyse the effects of healthy lifestyle, characterized by a correct diet and by adequate physical activity program in type 2 diabetes patients. We analysed 25 sedentary type 2 diabetes patients subjected to a correct diet and therapeutic treatment and 20 active type 2 diabetes patients subjected to a correct nutrition and a program of physical activity. We found an amelioration in biochemical and anthropometric parameters such as blood pressure, glycemia, glycated haemoglobin, body mass index (BMI). Given these results we can conclude that the physical activity has always been considered one of the cornerstones of type 2 diabetes therapy together with diet and pharmacotherapy. However, the results obtained show that physical activity deserves the same level of consideration as diet and insulin therapy even in the subject with type 2 diabetes.